Pengaruh Media Peta Sejarah Interaktif dan Gaya Belajar Terhadap Hasil Belajar Siswa SMP di Kota Bekasi - Arinarita Peni Andaryati (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2016)
The aim of this research is to determining the influence of media learning interactive historical map and learning style to the result of history learning through IPS subject in class IX. The method used in this research is the experimental method, a 2X2 treatment design by level. The validity and reliability are tested by Pearson Product Moment and Alpha Cronbach. The results of this research are (1) the results of historical learning outcomes students using interactive historical maps and have higher visual learning style of students who use historical maps interactive media and have auditory learning style. (2) the results of historical learing outcomes students who have higher auditory learning styles of students who have a visual learning style on instruction using conventional media, (3) There is an interaction effect the use of interactive historical maps on historical learning outcomes.